THE USE OF PEER ASSESSMENT AND REFLECTIVE DISCUSSION TO IMPROVE STUDENT PARTICIPATION AND ORAL PRESENTATION PERFORMANCE IN A TECHNICAL COMMUNICATION CLASSROOM - Chiew Yen, Dwee (Journal of Techno-Social, 2015)
21st century classrooms are gearing towards student-centered classrooms where learning is deemed to be more meaningful when students are actively engaged in their learning. In a bid to create more student-centered classrooms, the researcher decided to explore the use of peer assessments and reflective discussions in a Technical Communication classroom as part of an action research to improve student participation and oral presentation performance among thirty 18-year-old diploma students studying in Universiti Tun HusseinOnn Malaysia. The study revealed students in general have a positive perception towards the use of peer assessment and reflective discussion in the classroom. In addition to increased participation and attentiveness in class, improvement in oral presentation performance for the majority of the students (73.3%) was observed. This research shows that with careful planning and scaffolding, positive results can be achieved by employing these two techniques in the teaching and learning process.